2005
DOI: 10.1103/physreve.72.021408
|View full text |Cite
|
Sign up to set email alerts
|

Cluster formation of nanoparticles in an optical trap studied by fluorescence correlation spectroscopy

Abstract: We report in situ observation of cluster growth of nanoparticles confined in an optical trapping potential by means of fluorescence correlation spectroscopy. When an optical trapping force caused by a highly focused laser beam acts on nanoparticle suspensions, the number of nanoparticles increases and an assembly can be formed at the focal spot. The decay times of fluorescence autocorrelation curves were investigated as a function of the irradiation time of the laser beam and the laser power. In the initial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
68
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 29 publications
2
68
0
Order By: Relevance
“…[1][2][3] Over the past decades, the study on photon pressure in solution has progressed with the size reduction of target materials from microscale to nanoscale, [4][5][6] and actually, we have extended a series of experiments on the dynamics of photon pressure-induced association of nanoparticles, polymers, micelles, and J-aggregates in their solutions at room temperature. [7][8][9][10][11] As an example, polystyrene latex nanoparticles with 24 nm diameter were trapped and gathered by photon pressure, leading to their assemblies in a focal spot. 11 In single-molecule level, Osborne et al and Chirico et al separately reported that the diffusion of Rhodamine 6G molecules in the focal spot were suppressed under photon pressure, although no stable trapping was achieved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Over the past decades, the study on photon pressure in solution has progressed with the size reduction of target materials from microscale to nanoscale, [4][5][6] and actually, we have extended a series of experiments on the dynamics of photon pressure-induced association of nanoparticles, polymers, micelles, and J-aggregates in their solutions at room temperature. [7][8][9][10][11] As an example, polystyrene latex nanoparticles with 24 nm diameter were trapped and gathered by photon pressure, leading to their assemblies in a focal spot. 11 In single-molecule level, Osborne et al and Chirico et al separately reported that the diffusion of Rhodamine 6G molecules in the focal spot were suppressed under photon pressure, although no stable trapping was achieved.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] As an example, polystyrene latex nanoparticles with 24 nm diameter were trapped and gathered by photon pressure, leading to their assemblies in a focal spot. 11 In single-molecule level, Osborne et al and Chirico et al separately reported that the diffusion of Rhodamine 6G molecules in the focal spot were suppressed under photon pressure, although no stable trapping was achieved. 12,13 These results imply that photon pressure efficiently works even on small clusters or molecules, which have the sizes much smaller than the wavelength of the trapping laser.…”
mentioning
confidence: 99%
“…This is called optical tweezers or optical trapping. Nanoparticles whose diameter is much less than the laser wavelength can be trapped as a group in the laser focus and their aggregates formed (Hosokawa et al 2005;Yoshikawa et al 2004;Tanaka et al 2009). We utilize the aggregation of Ag nanoparticles in an optical trap to analyze molecules adsorbed on the aggregates based on surface-enhanced Raman scattering (SERS) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1980s, we demonstrated laser trapping of micrometer-sized particles in view of chemistry, developed various methodologies for their manipulation, ablation, and patterning in solution, and elucidated their dynamics [2]. Our trials were the first systematic study on spectroscopy and chemistry in small domains, and, in the middle of the 1990s, we started laser trapping studies on polymers, micelles, dendrimers, and nanoparticles of gold and polymers [3][4][5][6][7]. The 1064-nm laser irradiation gathers these nano-objects in solution and fills up just the focal volume, forming their assembly [8,9].…”
Section: Introductionmentioning
confidence: 99%